Lesson Learned from Japan for Flood Disaster Risk Reduction in Indonesia - Haruming Tyas, Titisari; Sutisna, Sobar; Supriyatno, Makmur; Widana, I Dewa Ketut Kerta; Fatkul Fikri, Ahmad (Technium Social Sciences Journal, 2022)
Indonesia and Japan have experienced hydrometeorological disasters, primarily floods disasters every year. The two countries must experience few losses due to improper disaster management. However, along with the times, Japan, an expert in technology development, can reduce flood risk. Japan has established itself as a country that is an example for countries in disaster risk reduction. The Japanese government promotes a concept, namely "Build Back Better" to build a post-disaster area to restore the area to its original state and take opportunities to develop better than before. Meanwhile, Indonesia, a developing country incidentally, is still trying to reduce the risk of flood disasters that cause considerable losses to the nation. Therefore, this study aims to analyze the lessons learned from Japan for flood risk reduction in Indonesia. This study uses a qualitative descriptive method with data collection techniques through Focus Group Discussions (FGD) with professors and researchers from Japan and reviewing disaster risk reduction documents. The results of this study indicate that there are several keys to success that Japan has in reducing flood risk, such as a) a mindset to be able to make disasters a challenge for the better; b) policies and disaster management systems structure from the center to the regions; c) encourage the development of SETI (Science, Engineering, Technology, and Innovation) for disaster risk reduction to many sectors; and d) Japan’s ambition in implementing Society 5.0 which is relevant to Disaster Risk Management (DRM).